Pengaruh Kepemimpinan dan Iklim Organisasi Terhadap Komitmen Pegawai pada Dinas Ketenagakerjaan Kota Tasikmalaya - Dewi Yulianti; Barin Barlian; Evilia Sri Yuniar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the era of globalization, public organizations such as the Manpower Office of Tasikmalaya City face complex challenges. Effective human resource (HR) management is key to achieving organizational goals and providing the best possible service. Employee commitment, which is influenced by leadership and organizational climate, is an important factor in achieving this. This research aims to analyze the influence of leadership and organizational climate on employee commitment in the Manpower Office of Tasikmalaya City. This research uses a quantitative method with a survey data collection technique through questionnaires to 45 employees. The data was analyzed using the multiple linear regression analysis technique. The results of the study show that leadership and organizational climate have a significant simultaneous and partial influence on employee commitment. This means that good leadership and organizational climate can increase employee commitment. This research provides important implications for the Manpower Office of Tasikmalaya City in increasing employee commitment through effective leadership and organizational climate. This can contribute to improving performance and achieving organizational goals.